Management of Dyspnea in Patients with Neuromuscular Disorders - Scullin, Daniel; Barney, Joseph (Seminars in Respiratory and Critical Care Medicine, 2025)
Neuromuscular diseases encompass a wide array of clinical manifestations, age at presentation, and severity of morbidity and mortality. Central to most patients with these disorders are symptoms of dyspnea and increased work of breathing related to varying degrees of impairment of the neuromuscular apparatus. The degree of dyspnea is often compounded by impaired clearance from the tracheobronchial tree, leading to patients who are weak, dyspneic, and impacted by pulmonary secretions. Approaches to determining contributing causes and management of dyspnea in these patients vary among adult and pediatric patients and are also distinct depending on the natural progression of the specific neuromuscular disorder. We describe an approach to the management of dyspnea in patients with neuromuscular diseases and review the roles of pharmacologic and respiratory support devices in alleviating symptoms and supporting respiration.
Keywords: neuromuscular; dyspnea; respiratory failure; ventilation; bronchopulmonary clearance